Comparison of Tools for Nutritional Assessment and Screening of Hospitalized Patients: A study on Surgical Patients - Susetyowati SUSETYOWATI; Amalia Sarah SHOLIKHATI; Dinda Krisma CAHYANINGRUM; Azizah Isna RACHMAWATI; Adeodatus Yuda HANDAYA (Medeniyet Medical Journal)
Objective: To compare the Simple Nutrition Screening Tool (SNST) with other nutritional screening tools [Nutrition Risk Screening 2002 (NRS- 2002), Nutrition Risk index (NRI)], nutritional assessment parameters, and the Subjective Global Assessment (SGA) in surgical patients. Methods: A comparative observational study with a total of 122 surgical patients. Patients were assessed during the first 24 h of admission in the ward from January to July 2022 using the NRI, NRS-2002, SNST, body mass index (BMI), mid-upper arm circumferences (MUAC), albumin serum, hemoglobin level, total lymphocyte count (TLC), and SGA. Sensitivity, specificity and predictive values were calculated to evaluate NRI, NRS- 2002, SNST, BMI, MUAC, albumin, hemoglobin, TLC compared to SGA. Results: The screening tools identified a high nutritional risk in surgical patients from 58.2%-72.1%. Meanwhile, about 29.5% to 71.3% was affected by malnutrition based on nutritional assessment tools. There were significant associations between the type of disease, the screening tools, the anthropometric parameters, albumin, TLC as well and SGA (p<0.05). The SNST has a good category among the nutritional screening tools with sensitivity and specificity >80%, as well as area under the curve >0.8. Conclusions: There were significant associations for screening (NRS- 2002, SNST) and nutritional assessment tools (BMI, MUAC, albumin) compared with SGA. Both these tools can be used to determine the risk of malnutrition in surgical patients.